The Auriga stellar haloes: connecting stellar population properties with accretion and merging history. Issue 2 (26th February 2019) - Monachesi, Antonela; Gómez, Facundo A; Grand, Robert J J; Simpson, Christine M; Kauffmann, Guinevere; Bustamante, Sebastián; Marinacci, Federico; Pakmor, Rüdiger; Springel, Volker; Frenk, Carlos S; White, Simon D M; Tissera, Patricia B
Abstract: We examine the stellar haloes of the Auriga simulations, a suite of 30 cosmological magnetohydrodynamical high-resolution simulations of Milky Way-mass galaxies performed with the moving-mesh codearepo . We study halo global properties and radial profiles out to ∼150 kpc for each individual galaxy. The Auriga haloes are diverse in their masses and density profiles, mean metallicity and metallicity gradients, ages, and shapes, reflecting the stochasticity inherent in their accretion and merger histories. A comparison with observations of nearby late-type galaxies shows very good agreement between most observed and simulated halo properties. However, Auriga haloes are typically too massive. We find a connection between population gradients and mass assembly history: galaxies with few significant progenitors have more massive haloes, possess large negative halo metallicity gradients, and steeper density profiles. The number of accreted galaxies, either disrupted or under disruption, that contribute 90 per cent of the accreted halo mass ranges from 1 to 14, with a median of 6.5, and their stellar masses span over three orders of magnitude. The observed halo mass–metallicity relation is well reproduced by Auriga and is set by the stellar mass and metallicity of the dominant satellite contributors. This relationship is found not only for the accreted component but also for the total (accreted + in situ ) stellar halo. Our results highlight the potential of observable halo properties to infer the assembly history of galaxies.